2020
DOI: 10.1017/s0007114520002883
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria assessment of pea protein quality in rats: a comparison between casein, gluten and pea protein alone or supplemented with methionine

Abstract: The objective of this study was to assess the nutritional quality of pea protein isolate in rats and to evaluate the impact of methionine (Met) supplementation. Several protein diets were studied: pea protein, casein, gluten, pea protein-gluten combination and pea protein supplemented with Met. Study 1: Young male Wistar rats (n = 8/group) were fed the test diets ad libitum for 28 days. The Protein Efficiency Ratio (PER) was measured. Study 2: Adult male Wistar rats (n = 9/group) were fed the test diets for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…First, the apparent and true digestibilities of pea proteins were in the same range of values of the other proteins. Recent studies have reported that pea protein is highly digestible in rats [18,23]. However, this work represents one of the first studies to show that pea protein is also highly digestible in old rats.…”
Section: Nitrogen Balance Digestibility and Rate Of Utilizationmentioning
confidence: 69%
See 1 more Smart Citation
“…First, the apparent and true digestibilities of pea proteins were in the same range of values of the other proteins. Recent studies have reported that pea protein is highly digestible in rats [18,23]. However, this work represents one of the first studies to show that pea protein is also highly digestible in old rats.…”
Section: Nitrogen Balance Digestibility and Rate Of Utilizationmentioning
confidence: 69%
“…However, this work represents one of the first studies to show that pea protein is also highly digestible in old rats. It has been suggested that the digestibility of plant proteins is impaired due to the presence of both anti-nutritional factors and indigestible fractions in their sequence [23]. However, the pea protein used here was a protein isolate, and protein isolates are generally well-digested [24].…”
Section: Nitrogen Balance Digestibility and Rate Of Utilizationmentioning
confidence: 99%
“…Pea protein isolate has a reported PER of 1.14, which increased to 2.52 upon supplementation with methionine to the same amount present in casein, which has a PER of 2.55. PDCAAS, calculated using true fecal nitrogen digestibility values, and DIAAS, calculated using true cecal amino acid digestibility values, for pea protein isolate are 1.02 and 0.88, respectively (Guillin et al, 2021). DIAAS values determined in pigs instead of rats showed that proteins from animal (dairy) source (1.0-1.2) exhibited higher values than proteins from soy, pea, or wheat (0.45-0.89) (Mathai et al, 2017).…”
Section: Protein Qualitymentioning
confidence: 96%
“…The Panel notes that mung bean protein is well digestible (Moughan et al., 2012 ; Rutherfurd et al., 2012 , 2015 ; Devi et al., 2018 ; Kashyap et al., 2019 ; Shivakumar et al., 2019 ). It provides sufficient amounts of most essential amino acids but only limited amounts of sulfur‐containing amino acids, and for this reason, the PDCAAS of the NF is lower than that for other legume proteins (Hughes et al., 2011 ; Guillin et al., 2021 ; Rutherfurd et al., 2015 ). Based on the highest (max.…”
Section: Assessmentmentioning
confidence: 99%